2020
DOI: 10.1016/j.cmet.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tumor Initiation by the Mitochondrial Pyruvate Carrier

Abstract: Highlights d Intestinal tumors exhibit low MPC expression d MPC inactivation is sufficient to promote intestinal tumor formation in mice and flies d MPC overexpression in the fly is sufficient to prevent oncogene-induced tumorigenesis d MPC expression correlates negatively with expression of Wnt/b-catenin target genes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 73 publications
4
107
0
Order By: Relevance
“…This initial event was associated with hyperactivation of the Wnt/β-catenin pathway and loss of function of the APC tumor suppressor. In this study, expression of both MPC1 and MPC2 was found to be decreased in adenomas in two different mouse models of colon cancer, the azoxymethane and dextran sodium sulfate (AOM-DSS) models, as well as a genetic model of heterozygous loss of Apc in intestinal stem cells (Apc Lrig1KO/+ Mpc1 Lrig1KO mice) [94]. Targeted deletion of MPC1 in adult LRIG1 + intestinal stem cells (Mpc1 Lrig1KO ) led to an increased tumor burden and a substantial increase in the incidence of macroscopic tumors in the AOM-DSS model.…”
Section: The Role Of Mpc In Stemnessmentioning
confidence: 88%
See 1 more Smart Citation
“…This initial event was associated with hyperactivation of the Wnt/β-catenin pathway and loss of function of the APC tumor suppressor. In this study, expression of both MPC1 and MPC2 was found to be decreased in adenomas in two different mouse models of colon cancer, the azoxymethane and dextran sodium sulfate (AOM-DSS) models, as well as a genetic model of heterozygous loss of Apc in intestinal stem cells (Apc Lrig1KO/+ Mpc1 Lrig1KO mice) [94]. Targeted deletion of MPC1 in adult LRIG1 + intestinal stem cells (Mpc1 Lrig1KO ) led to an increased tumor burden and a substantial increase in the incidence of macroscopic tumors in the AOM-DSS model.…”
Section: The Role Of Mpc In Stemnessmentioning
confidence: 88%
“…More recently, MPC was shown to be involved in the initiation of intestinal tumor formation in mice and Drosophila [94]. Sporadic colon tumors are believed to follow a typical progression pathway in which the initial tumorigenic event triggers intestinal stem-cell hyperplasia, leading to the formation of a benign adenoma.…”
Section: The Role Of Mpc In Stemnessmentioning
confidence: 99%
“…Several crucial processes and signaling pathways have been identified by GO enrichment analysis, caffeine metabolism, metabolic pathways, and KEGG pathway analysis including oxidation-reduction and the xenobiotic metabolic process. Previous research demonstrated that the oxidation-reduction process and xenobiotic metabolic process play a crucial role in the development of CRC or colorectal cancer cells (Bensard et al, 2020;Han et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that multiple cancers exhibited diminished MPC expression and activity, which causing dysfunction of mitochondrial pyruvate uptake. High glycolysis of tumor cells is known as the Warburg effect and the MPC is likely involved in the Warburg effect, which offers a potential target for cancer therapy [29][30][31]. Growing evidence supported that the altered mitochondrial function and the Warburg effect were closely correlated in the development of DN [32].…”
Section: Discussionmentioning
confidence: 99%